Offshore wind turbine operations and maintenance: A state-of-the-art review. (July 2021) - Ren, Zhengru; Verma, Amrit Shankar; Li, Ye; Teuwen, Julie J.E.; Jiang, Zhiyu
Abstract: Operations and maintenance of offshore wind turbines (OWTs) play an important role in the development of offshore wind farms. Compared with operations, maintenance is a critical element in the levelized cost of energy, given the practical constraints imposed by offshore operations and the relatively high costs. The effects of maintenance on the life cycle of an offshore wind farm are highly complex and uncertain. The selection of maintenance strategies influences the overall efficiency, profit margin, safety, and sustainability of offshore wind farms. For an offshore wind project, after a maintenance strategy is selected, schedule planning will be considered, which is an optimization problem. Onsite maintenance will involve complex marine operations whose efficiency and safety depend on practical factors. Moreover, negative environmental impacts due to offshore maintenance deserve attention. To address these issues, this paper reviews the state-of-the-art research on OWT maintenance, covering strategy selection, schedule optimization, onsite operations, repair, assessment criteria, recycling, and environmental concerns. Many methods are summarized and compared. Limitations in the research and shortcomings in industrial development of OWT operations and maintenance are described. Finally, promising areas are identified with regard to future studies of maintenance strategies. Highlights: Review of strategies, planning, operations, and environmental effects of offshore wind turbine operation and maintenance. Maintenance strategies are introduced, including corrective, proactive, and opportunistic. The development and limitations of the optimal scheduling problem are discussed. The crew and equipment transferring, docking, and lifting operations are analyzed.